Justice for the Survivors: Examining the Effectiveness of the Adopted University Policy in Serving Justice on Gender-Based Violence Cases at a Selected South African University - Gwiza, Memory; Hendricks, Eleanor A. (Social and Health Sciences, 2025)
Incidences of gender-based violence (GBV) on university campuses have become endemic. Although some universities developed policies to manage the scourge of GBV on their campuses, the effectiveness of such policies in serving justice to the victims of GBV remains controverted. This study examined the perceived effectiveness of an adopted policy and its implementation in serving justice for the victims of GBV at a selected South African university. A radical feminist perspective underpinned this research. A qualitative research methodology with semi-structured self-administered interviews was used to collect data from 10 purposefully sampled participants: two victims of GBV, two staff members from the GBV unit, the counselling unit and the HIV unit, and two members of the South African Police Service (SAPS). Using a thematic analysis, the study found that the implementation of the adopted policy at the selected university failed to ensure effective reporting of GBV incidents. It also did not serve the appropriate justice for the victims of GBV by punishing the perpetrators of GBV or by rendering adequate support to the survivors of GBV. The research recommends enacting multi-sectoral approaches, ensuring increased training on the processes to be followed, and evaluating the relevant policy management and implementation of the GBV policy at the university regularly. The university should change the sociocultural environment on campus to one of zero tolerance towards GBV and any other form of violence. Better implementation of the policy, collaboration with the SAPS and transparent dealings with perpetrators will lead to enhanced justice for victims.